Frequency of thalassemia carrier and Hb variant and the quality of stored donor blood (Medical Journal of Indonesia, 2014)
Background: This study was aimed to determine the frequency of thalassemia and Hb variant in blood donor. In addition, we also wanted to know the quality of blood from the donor up to seven days of storage, by calculating percentage of hemolysis in vitro. Methods: This cross-sectional study was conducted on 138 blood donor specimens at Red Cross Blood Centre Unit in Jakarta. All specimens were tested for thalassemia and Hb variant by complete blood count (CBC) and Hb analysis with HPLC method and DNA analysis for the detection of α thalassemia carrier. To analyze the quality of stored blood, the calculation of hemolytic rate of red blood cells (RBCs) on whole blood (WB) was compared between the first and seventh days of storage. Results: Out of the 138 specimens, 5 samples (3.6%) were diagnosed for α thalassemia carrier in which, one of them is co-inherited with ovalositosis hereditary (Southeast Asian Ovalositosis/SAO), 3 samples (2.2%) for β thalassemia carrier, and 3 samples (2.2%) for Hb E. Meanwhile, the hemolytic rates of RBCs on WB in first day and seven day of storage were below one percent. Conclusion: The frequency of thalassemia carrier and Hb variants in blood donors at Red Cross Blood Centre Unit in Jakarta was 8%. The quality of stored blood until seven day of storage was quite good.